EFFECT OF CRYSTALLITE SIZE ON SOLID STATE MISCIBILITY: APPLICATIONS TO THE PYRITE-CATTIERITE SYSTEM - Tauson V.L.; Akimov V.V. (My University, 1991)
The miscibility gap in the FeS 2 -CoS 2 system has been studied for various crystallite sizes. The pyrite-cattierite solvus for bulk phases is strongly asymmetric and has a critical point of ~740°C and ~ 13 mol% CoS 2 . As shown from previously published data the critical point for small particles ( 0.05 m) occurs at 650°C or lower where the binodal curve becomes more symmetrical. Theoretical consideration of equilibrium conditions of coexisting solid solutions in a binary small-phase system in terms of generalized chemical potentials permits derivation of a system of nonlinear equations from which the compositions of coexisting solid solutions can be determined for any crystallite size. The data obtained give evidence for a crystallite size effect; that is, phase relations (particularly, phase boundary position) are dependent upon the crystallite size in a given mineral system. These observations are important in establishing phase boundaries under high pressure-high temperature conditions when finely dispersed starting materials are used. It appears that the crystallite size effect may be responsible for certain anomalies of solid state miscibility in mineral systems, for example, the formation of supersaturated crystalline solutions.